(untitled) (Journal of Medical & Health Sciences Review, 2025)
Chikungunya virus (CHIKV), and α-virus transmitted by mosquitoes, has re-emerged recently, causing significant global outbreaks. Infection leads to CHIKV fever (CHIKF), an acute febrile illness primarily characterized by arthritis and myalgia, which can persist for days to months. The pain is much more pronounced and localized to the joints and tendons in CHIKV fever. Although CHIKF is usually self-limiting, severe cases with complications like persistent arthralgia, neurological manifestations and fatalities have been documented. The risk of a person transmitting CHIKV to an uninfected mosquito is highest in the first week of the illness. The virus’s resurgence is likely driven by factors such as viral evolution, globalization and climate change, exacerbated by the absence of licensed vaccines or antiviral therapies. The presence of co-circulating viruses, such as dengue and Zika, complicates diagnosis due to symptom overlap. In light of its expanding range and unpredictable outbreaks, CHIKV has become a major global health threat. No any specific treatment or vaccines are available, only preventive is protection against mosquito bites. The main objective of this review article is to integrate historical, clinical and ecological perspectives on the CHIKV virus to enhance understanding and drive future research priorities. Moreover, this review covers recent advancements in understanding CHIKV pathogenesis, epidemiology, atypical disease manifestations and the progress and challenges in developing effective CHIKV vaccines.